ANALISA SIFAT KIMIA DAN FISIK MODIFIED CASSAVA FLOUR (MOCAF) (VARIETAS LOKAL SANGKOLA) ASAL DESA WAAI, MALUKU TENGAH - Cynthia G C Lopulalan; Meitycorfrida Mailoa; Halija Pelu (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
This study aimed to determine the method of making ‘Mocaf’ (Modified Cassava Flour) flour that was in accordance the quality standards (SNI 01-2997-1992). This study used a Randomized Block Design consisting of one factor, namely was the flouring methos consisting of four treatments: namely drying, water immersion, lime water immersion, and curing. The data were statistically tested using the analysis of variance according to the design used, followed by the Honestly Significant Difference test. Based on the research results, the best treatment of this research was lime water immersion treatment, which produced ash content of 0.74%, carbohydrate content 82.68%, HCN content 0.05% and whiteness 91.32%.